慢性Ｂ型肝炎感染症を処置または防止するための複数抗原治療ワクチン (2025)
本発明は、慢性Ｂ型肝炎（ＣＨＢ）の処置のための治療的免疫のための組成物および方法に関する。本発明の方法は、高力価ハイブリッドＢ型肝炎ウイルス（ＨＢＶ）ベクターを作製する方法、ＨＢＶ感染症および／またはＣＨＢを処置および／または防止する方法、ならびにそれにより作製されたＶＬＶ組成物を投与された対象においてＨＢＶ感染症に対するメモリーＴ細胞およびメモリーＢ細胞の免疫応答を誘導する方法を含む。さらに、本発明は、ＨＢＶによる感染症に対して対象を保護するためにその対象にワクチン接種するための医薬組成物を含む。 The present invention relates to compositions and methods for therapeutic immunization for treatment of chronic hepatitis B virus (CHB). Methods of the invention include a method generating a high titer hybrid-hepatitis B virus (HBV) vector, methods of treating and/or preventing HBV infection and/or CHB, and methods of inducing a memory T and B cell immune response against HBV infection in a subject administered the VLV composition produced thereby. Furthermore, the invention encompasses a pharmaceutical composition for vaccinating a subject to protect the subject against infection with HBV.